Choroidal neovascular membranes secondary to intraocular tuberculosis misdiagnosed as neovascular age-related macular degeneration. Issue 2 (March 2018) - Invernizzi, Alessandro; Agarwal, Aniruddha; Di Nicola, Maura; Franzetti, Fabio; Staurenghi, Giovanni; Viola, Francesco
Purpose: Intraocular tuberculosis (IOTB) can be complicated by choroidal neovascularization (CNV). However, when the CNV development is not accompanied by clear signs of inflammation, the etiology can be missed, especially in countries nonendemic for tuberculosis. We describe the clinical and imaging features of CNVs presenting as the first sign of IOTB initially misdiagnosed as exudative age-related macular degeneration (AMD). Methods: A retrospective review of clinical and imaging data of patients initially misdiagnosed with neovascular AMD later diagnosed with inflammatory CNV secondary to IOTB at tertiary referral centers was conducted. Features of fundus photography, fluorescein angiography, indocyanine green angiography, and enhanced depth imaging optical coherence tomography were analyzed. Distinguishing features between neovascular AMD and IOTB-associated CNV were evaluated. Results: Five patients over 55 years of age, erroneously diagnosed with exudative AMD, were included in the study. Multimodal imaging analysis allowed identification of peculiar choroidal alterations such as choroidal granulomas or choroiditis suggestive for posterior uveitis. Systemic workup for granulomatous uveitis including immunologic investigations such as tuberculin skin test or QuantiFERON TB Gold® and radiologic investigations revealed tubercular etiology in all the cases, allowing correct diagnosis and management of the uveitis and related CNV. Conclusions: Choroidal neovascularization represents a rare and unusual presenting sign of IOTB that can be misleading especially when it occurs in the elderly living in countries with low prevalence of the disease. Multimodal imaging can be helpful and should be employed, especially in atypical cases of CNV, in order to avoid misdiagnosis and/or diagnostic delays.